Lifelong Learning towards the Achievement of Environment and Sustainable Development in Ghana - Donkoh, Ruth; Twerefoo, Portia Oware; Donkor, Josephine; Boateng, Solomon A; Lee, Wing On (International Journal of Educational Development in Africa, 2022)
The government of Ghana has demonstrated its ambition to achieve Sustainable Development Goals SDGs—presently a global catch-cry—through numerous educational developments. However, Ghana still battles with the tensions of environmental degradation such as illegal mining, water pollution, bad farming practices, and improper waste disposal, among several others. Therefore, this paper explores lifelong learning and sustainable development in Ghana. This is done through the implementation of retrospective literature evaluation and qualitative methods. The paper employs available literature and a hands-on study, which commences by tracking the history of lifelong learning, the importance of lifelong learning, and how Ghana demonstrates its support of lifelong learning to ensure sustainable development. A critical analysis is conducted on the reasons why Ghana persistently battles with environmental degradation. Numerous examples are presented as evidence to support the findings and formulate recommendations. The identification of these obstacles to achieving SDGs will enable the government, policymakers and citizens of Ghana to contribute their quota to the achievement of SDGs. This study will also help Ghana to redeem its natural resources, which have deteriorated over time.